Ємнісний накопичувальний пристрій у контурі збудження синхронної машини для форсування та гасіння поля - Слободенюк, Д.В.; Бялобржеський, О.В. (Електротехніка і електромеханіка, 2015)
В роботі проаналізовано існуючі силові схеми регулювання струму збудження синхронних двигунів. Розглянуто питання використання накопичувального пристрою в контурі обмотки збудження, на підставі чого запропоновано структуру системи керування динамічними режимами збудження синхронного двигуна, що дозволяє підтримувати заданий струм збудження синхронного двигуна певний період часу, за рахунок енергії конденсатора, введеної в контур збудження транзисторним перетворювачем. В работе проанализированы существующие силовые схемы регулирования тока возбуждения синхронных двигателей. Рассмотрены вопросы использования накопительного устройства в контуре обмотки возбуждения, на основании чего предложено структуру системы управления динамическими режимами возбуждения синхронного двигателя, позволяющей поддерживать заданный ток возбуждения синхронного двигателя определенный период времени, за счет энергии конденсатора, введенной в контур возбуждения транзисторным преобразователем. Purpose. Development of circuitry and control system with capacitive storage device in the exciting circuit of the synchronous motor for forcing and blacking out the field. Methodology. Mathematical modeling of transient process in dynamic modes in exciting coil of the synchronous motor with taking into consideration the flux linkage in the exciting circuit and analysis of the received results, possible future researches in this field. Results. This paper analyzes the existing loading patterns of regulating exciting current of the synchronous motors. The authors study the issues of applying the storage device in the circuit coil and suggest the structure of the system of controlling dynamic modes of exciting synchronous motor which allows maintaining the specified synchronous motor exciting circuit during a certain period of time due to the capacitor energy introduced into the exciting circuit by a transistor converter. A mathematical model of the suggested device has been developed. There have been received diagrams of the transient process by modeling dynamic modes. Originality. The authors suggest the system of exciting with the storage condenser to apply effectively the compensative ability and enhance stability of the synchronous engine by regulating the exciting circuit in the dynamic modes. Practical value. On the basis of the conducted investigations the device ensures two-way transmission of energy between the exciting coil and capacitor with high characteristics of the circuit change speed which can provide sufficient characteristics for enhancing the automatic control system performance of exciting the synchronous motor is developed.